Optimalisasi Kemanfaatan Riset Hukum bagi Upaya Peningkatan Kesadaran Hukum Masyarakat yang Berkesejahteraan - Handoyo Prasetyo; Bambang Waluyo; Binsar Jon Vic S; Subakdi Subakdi (Lembaga Pengembangan Kinerja Dosen, 2026)
Doctoral legal research often gets trapped in academic formality and lacks practical benefit for the public. This Community Service (PKM) activity aims to optimize the utility of legal research through educational dissemination on the axiology of philosophy of science and the enhancement of practical legal awareness among residents of Cilempuk Hamlet, Purwamekar Village, Karawang Regency. The implementation method employed a participatory educational approach comprising socialization, interactive presentation on the Trias Philosophy of Science (ontology, epistemology, and axiology as the crown of a dissertation), and an open legal discussion. The results indicated an increased public understanding regarding the significance of axiological value (